Effects on different full-coverage designs and materials of crack propagation in first mandibular molar: an extended finite element method study - Ni, Jianzhao; Xu, Liang; Lin, Yunzhi; Lai, Danlin; Huang, Xiaohong (Frontiers in Bioengineering and Biotechnology, 2023)
This study investigated the effectiveness of five different full-coverage restorations in protecting cracked teeth. The authors used 3D modeling and simulations to test the fracture resistance of five different restoration designs made from three different materials (zirconia, lithium disilicate, and a hybrid polymer-infiltrated ceramic network material). The results showed that full-coverage restorations can significantly increase the fracture resistance of a cracked tooth, and the high strength of the restoration material (zirconia) plays a significant role in protecting the underlying cracked tooth. Furthermore, onlay restorations were shown to be highly effective in preventing dentin cracks from continuing to develop. The study's contribution to the field is the demonstration of the importance of choosing the right restoration material and design for protecting cracked teeth. The findings could aid in the selection of appropriate restorative materials and techniques to improve the clinical outcomes of patients with cracked teeth. The research could also serve as a starting point for further studies in this area, focusing on the optimization of restorative materials and designs to enhance the biomechanical properties of cracked teeth.